The Application of Four Corner Debate to Teach Speaking - Nury Kurnia (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2018)
The research aims at knowing and finding whether or not the application of four corner debate is effective to improve students speaking skill at the eighth grade students of SMP Jamaluddin ArRumi Jatisari Jenggawah Jember in academic year 2016/2017. The population of the study was 78 students with the number of sample 31 students in class VIII B. The research was a preexperimental research in which only one class which was treated using the technique. The data collection was administered through conducting speaking test and scored students performance. Afterwards the scores were converted to the school passing grade and then calculated in paired ttest. The result showed some data including students average score in pretest and posttest. The average score in pretest was 67.59 and 76.15 in posttest. It indicated an improvement for 8.65 points. The result of paired ttest calculation was 8.61 and the ttable score was 1.697with 0.05 significance level of score and DF 31 (32 to 1). The score analysis indicated that the ttest score was higher than the t-table score. Therefore, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was approved which means the application of four corner debate in the classroom is effective to teach English speaking to the eighth grade students of SMP Jamaluddin ArRumi Jatisari Jenggawah Jember in academic year 2016/2017. Keywords: four corner debate, English speaking, teaching speaking